Bank Liquidity and Financial Performance of Deposit Money Banks in Nigeria - E. O. , Efemena; C.I., Augustine (International Journal of Scientific Research and Management (IJSRM), 2024)
Due to the importance of the deposit money bank to the Nigerian Economy that liquidity level and status of this sector is not only important to the investors, the bank itself but also to the economy at large. Based on this challenge this study examines into the impact of bank liquidity on financial performance of deposit money banks in Nigeria. The secondary data was sourced from the audited financial statement of deposit money banks from 2018 to 2022. The study employed the static panel regression analysis to determine the relationship between liquidity ratio, loan-to-deposit ratio and bank size and financial performance measures. The findings from model one reveals that loan-to-deposit ratio and liquidity ratio has negative and positive significant effect on earnings per share, while loan-to-deposit ratio, liquidity ratio and bank size has negative significant effect on net interest margin.  It is therefore recommended that deposit money banks should carefully manage their loan-to-deposit ratios to avoid excessive lending that could negatively impact earnings per share. Institutions should focus on improving their liquidity ratios by maintaining sufficient liquid assets to meet short-term obligations. Enhancing liquidity management practices can positively affect earnings per share, boosting overall financial performance and shareholder value. Regularly monitoring and adjusting these ratios will ensure a balanced approach to lending and liquidity, supporting sustainable growth and profitability. Additionally, financial institutions should provide ongoing training and resources to their teams to strengthen risk management and financial planning.